2012
DOI: 10.3949/ccjm.79a.12017
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the elderly: Some practical considerations

Abstract: Data from randomized controlled trials suggest that treating hypertension in the elderly, including octogenarians, may substantially reduce the risk of cardiovascular disease and death. However, treatment remains challenging because of comorbidities and aging-related changes. We present common case scenarios encountered while managing elderly patients with hypertension, including secondary hypertension, adverse effects of drugs, labile hypertension, orthostatic hypotension, and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 54 publications
0
30
0
3
Order By: Relevance
“…Safety and tolerability of an antihypertensive drug are particularly important in elderly patients, as they are more likely to have renal and hepatic impairment that may affect the pharmacokinetics of the drug and suffer from orthostatic hypotension. 32 In the elderly population, first-line treatments are diuretics and long-acting calcium channel blockers, followed by ARBs. 29 Several studies have demonstrated that ARBs have greater efficacy and tolerability compared with other antihypertensive regimens in elderly populations; 33,34,35 for example, in the LIFE study, a losartan-based regimen was shown to have greater beneficial effects on BP and PP vs. an atenolol-based regimen in patients aged ≥67 years compared with patients aged <67 years.…”
Section: Discussionmentioning
confidence: 99%
“…Safety and tolerability of an antihypertensive drug are particularly important in elderly patients, as they are more likely to have renal and hepatic impairment that may affect the pharmacokinetics of the drug and suffer from orthostatic hypotension. 32 In the elderly population, first-line treatments are diuretics and long-acting calcium channel blockers, followed by ARBs. 29 Several studies have demonstrated that ARBs have greater efficacy and tolerability compared with other antihypertensive regimens in elderly populations; 33,34,35 for example, in the LIFE study, a losartan-based regimen was shown to have greater beneficial effects on BP and PP vs. an atenolol-based regimen in patients aged ≥67 years compared with patients aged <67 years.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt3 is a nuclear-encoded protein, however, the majority of Sirt3 translocates to mitochondria (29). Clinical studies have shown that Sirt3 expression declines by 40% by age 65 paralleling the increased incidence of hypertension (28, 30). Angiotensin II and inflammation also mediate the decline in Sirt3 activity (31).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that multiple risk factors for hypertension are associated with the reduced Sirt3 expression and activity. For example, Sirt3 activity is metabolically downregulated by increased Acetyl-CoA and reduced NAD + in metabolic syndrome, hyperlipidemia, diabetes and sedentary lifestyle while aging and smoking reduces Sirt3 expression (Figure 3) (30, 36*). It has been suggested that dietary supplementation of Sirt3 activating compounds such as resveratrol can be beneficial (37, 38).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Essential hypertension develops in ≈60% of individuals by the age of 60, but its characteristics in older people differ from those seen in the middle-aged, being associated more often with complications in the older-aged. 2 Hypertension is one of the most common known risk factors for orthostatic hypotension in the elderly persons. 3 Among the less studied risk factors for this orthostatic hypotension, poor vitamin D status is increasingly attracting interest because of recent research showing a strong relationship between serum 25-hydroxyvitamin D (25OHD) and blood pressure.…”
mentioning
confidence: 99%